Partnerships for Mental Health Narratives of Community and Academic Collaboration - Roberts, Laura Weiss; Reicherter, Daryn; Adelsheim, Steven; Joshi, Shashank V. (Springer International Publishing : Imprint: Springer, 2015)
This unique title richly tells the stories of partnership and collaboration. The narrative voice of each chapter derives from the people who tell their story -- immigrants, survivors of torture, mental health experts, urban people, rural people, teachers, doctors, attorneys, students, and international leaders. These authors provide emotionally powerful tales that move, affect, and encourage readers.  The collection of narratives is inspired by these individuals, who believe that collaboration can bring authentic mutualism, promise-keeping, and innovation to address the hardest problems we face as a world community.  Partnerships for Mental Health: Narratives of Community and Academic Collaboration is about the stories of innovation and collaboration occurring between community and academic partners who have undertaken among the very hardest of problems - such as the care of veterans with ravaging posttraumatic stress disorder; the care of homeless individuals with HIV, addiction, and mental illness; the care of caregivers for Hispanic family members with Alzheimer's disease; the prevention of illness in impoverished vulnerable youth; and the rescue of profoundly mentally ill earthquake survivors. In addition, this title not only also tells the story of identity formation of early-career physicians with a calling to work with distinct populations for whom suffering and stigma are immense, but also the stories of the special bonds that develop and are strengthened between community members and academic colleagues and, ultimately, between friends.  A truly indispensable contribution to the literature, this captivating and novel title illustrates and inspires collaboration in order to bring about better health outcomes for people affected by mental health issues in communities throughout the world.